Assessment of Geosynthetic Materials for Tunnel Drains: Laboratory Tests and Image Analyses - Jo, Youngseok; Cha, Wonjun; Yoo, Wan-Kyu; Kim, Bumjoo (KSCE journal of civil engineering, 2024)
Tunnel drainage systems are crucial design factors in tunnels because the accumulation of groundwater at the back of linings can affect tunnel safety. Geotextiles are used to facilitate the dissipation of pore-water pressure. However, chemical agents in the water can lead to clogging as tunnels age. In this study, laboratory tests and image analysis, namely Secondary Scanning Microscopy (SEM) and Energy-dispersive X-ray Spectrometry (EDS), were conducted to assess the drain performance of five geosynthetic materials: four geocomposites and one three-layered Non-Woven Needle-Punched (NWNP) geotextile. Calcium carbonate (CaCO 3 ) in liquids affects the discharge capacity of drains, and this capacity decreases with increasing confining pressure. NWNP geotextile is the most vulnerable to confining pressure as it lacks a core. The reason behind the significant decrease in the discharge capacity of NWNP geotextile is clarified based on the SEM analysis. EDS analysis investigated the major composition of the clogged materials, revealing that the primary components are carbon, oxygen, and calcium. Advanced imaging techniques can be utilized to gain a deeper understanding of the underlying mechanisms. The results of this study can aid in the design and maintenance of engineering systems, especially tunnel drainage systems, that incorporate geosynthetic materials.